2017
DOI: 10.12693/aphyspola.131.400
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Synthesis from Fish Bones: Atlantic Salmon (Salmon Salar)

Abstract: Production of the bioceramics on the market is presently conducted from typical precipitation method by using reagent grade raw chemicals or through calcination of natural sources like animal bones (especially bovine bone) and fish bones. Usually fish bones were damped near or in the water sources, which can lead to serious environmental pollution. Those were regarded as a trash, even though they still bear economic value, including conjugates. In this study bones of Atlantic Salmon (Salmo salar) were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
1
Order By: Relevance
“…Fish bones, which are made of 60% calcium orthophosphate, [36] can be refined through heat treatment to achieve a desired phase composition, such as HA or TCP (Figure 2a,b). [82][83][84][85][86][87][88][89][90] The pristine or treated fish bone powders have been used to fabricate porous HA [91] and porous biphasic calcium phosphate scaffolds. [92] They can also be incorporated into hydrogels, such as GelMA, [93] and alloys, such as Mg-Zn, [94] to form composites.…”
Section: Calcium Phosphate and Collagen From Fish Residuesmentioning
confidence: 99%
“…Fish bones, which are made of 60% calcium orthophosphate, [36] can be refined through heat treatment to achieve a desired phase composition, such as HA or TCP (Figure 2a,b). [82][83][84][85][86][87][88][89][90] The pristine or treated fish bone powders have been used to fabricate porous HA [91] and porous biphasic calcium phosphate scaffolds. [92] They can also be incorporated into hydrogels, such as GelMA, [93] and alloys, such as Mg-Zn, [94] to form composites.…”
Section: Calcium Phosphate and Collagen From Fish Residuesmentioning
confidence: 99%
“…Some of these extraction processes include calcination methods, alkaline hydrolysis, precipitation, hydrothermal or a combination of these techniques [ 16 ]. HA extracted from animal by-products has promising potential for various biomedical applications because it is biocompatible and bioactive [ 17 ]. Fish bones are an alternative that can be used to overcome the shortcomings of PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many considerations to be taken into account for heat treatment method such as heating profile of the raw material and optimum calcination temperature. There are many studies had been reported on the extraction of HAp using fish as an initial material [27][28][29][30], but none of the studies were carried out on the species of spotted sardinella (Amblygastersirm). The discovery of this new species of material for HAp extraction is needed to fulfil the gap of this research field.…”
Section: Introductionmentioning
confidence: 99%